Kepemimpinan Pendidikan Kompeten: Membangun Visi, Menghadapi Tantangan, Dan Meningkatkan Kualitas Pembelajaran Di Era Modern - Afifah Maharani; Salsabila Putry Zaen; Riezma Diant Amanah; A. Sayyirussalikin (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2024)
Educational leadership has a strategic role in determining the direction, quality, and success of education, especially in the modern era full of challenges. The background of this study is based on the urgent need for educational leaders who are able to respond to technological changes, social dynamics, and the demands of globalization. This article aims to describe how competent educational leadership can build a strong vision, face challenges, and improve the quality of learning at various levels of educational institutions. This article was written using a descriptive-qualitative method with a literature review approach. Data were collected from various sources such as scientific journals, books, research reports, and case studies that are relevant to the topic of educational leadership. The analysis was carried out to identify key elements of effective educational leadership, strategies to face modern challenges, and efforts to improve the quality of learning. The results of the study show that competent educational leaders have characteristics such as a clear vision, collaborative skills, and sensitivity to change. The main strategies identified include ongoing training for teachers, application of technology in the learning process, efficient resource management, and development of infrastructure that supports learning. With an integrated approach, competent educational leadership is able to create an innovative learning environment, improve student and teacher performance, and ensure that educational institutions can compete globally. This article provides practical recommendations for educational leaders in facing modern challenges and achieving educational goals optimally.